2012
DOI: 10.1111/j.1467-8624.2011.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Lions Have Manes? For Children, Generics Are About Kinds Rather Than Quantities

Abstract: Generic statements (e.g., “Lions have manes”) make claims about kinds (e.g., lions as a category) and, for adults, are distinct from quantificational statements (e.g., “Most lions have manes”), which make claims about how many individuals have the property in question. This paper examined whether young children also understand that generics do not depend purely on quantitative information. We compared 5-year-olds’ judgments about the truth/falsity of pairs of statements expressing properties that were matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 44 publications
2
52
0
1
Order By: Relevance
“…Children's early capacity to learn generics is particularly striking, given that generic referents are abstract (one cannot point to a kind, only to instances of a kind) and their semantics cannot be reduced to a particular quantity (unlike "some," "most," or "all") (43-45). For example, although "Lions have manes" is acceptable despite applying only to male lions, "Lions are male" is semantically unacceptable, and preschool children understand this (46).…”
Section: Categories As Cultural Inheritancementioning
confidence: 99%
See 1 more Smart Citation
“…Children's early capacity to learn generics is particularly striking, given that generic referents are abstract (one cannot point to a kind, only to instances of a kind) and their semantics cannot be reduced to a particular quantity (unlike "some," "most," or "all") (43-45). For example, although "Lions have manes" is acceptable despite applying only to male lions, "Lions are male" is semantically unacceptable, and preschool children understand this (46).…”
Section: Categories As Cultural Inheritancementioning
confidence: 99%
“…They have two semantic features that support essentialism: they express properties that are timeless and nonaccidental (e.g., "birds have hollow bones"), and they minimize within-category variability (e.g., "birds lay eggs," even though only adult females do so). Preschool children appreciate both these points (46,58). Moreover, hearing novel generics about novel categories leads to more within-category inferences (36,112), assumption of core features (57), and essentialist inferences about that category, above and beyond labeling per se (108,109).…”
Section: Two Presuppositions: Norms and Essencesmentioning
confidence: 99%
“…"lions have manes"). In a follow-up study, we converted all of the suggests that even for preschoolers, generics are not simple expressions of beliefs about prevalence (Brandone et al, 2012).…”
Section: Generics In Acquisitionmentioning
confidence: 99%
“…For example, Amanda Brandone, Andrei Cimpian, Susan Gelman and I found that adults are significantly more likely to accept sentences such as "birds lay eggs" (or "lions have manes," or "pigs give milk their young") than they are to accept sentences such as "birds are female" (or "lions are male," or "pigs are female"), despite appreciating that there are comparable numbers of female birds (or male lions, or female pigs) and egg-laying birds (or maned lions, or nursing pigs) (Brandone, Cimpian, Leslie & Gelman, 2012). That is, for a range of examples, participants understand that only one sex of the kind has a particular characteristic property, yet they are far more likely to accept a generic that predicates the characteristic property than they are to accept a generic that predicates belonging to that sex.…”
mentioning
confidence: 99%
“…The majority of children's utterances that express category content occur in self-initiated exchanges. (As a side note, the inference that certain linguistic structures [e.g., BBoys like trucks^] express thoughts about categories [e.g., BOYS, TRUCKS] is supported by decades of work in linguistics and philosophy [e.g., Carlson & Pelletier, 1995;Leslie, 2008], as well as in cognitive development [e.g., Brandone, Cimpian, Leslie, & Gelman, 2012]). Rather than being mere mimicry, children's category talk most likely reflects a deeper interest in gaining information at the category level-and, indeed, recent work has suggested that children are particularly eager to acquire knowledge about categories (Cimpian & Park, 2014;Cimpian & Petro, 2014; see also Martin & Ruble, 2004).…”
Section: How Plausible Is a Category-less Account Of Inductive Generamentioning
confidence: 99%